Managing smoking cessation Authors’ reply to letter - Aveyard, P; West, R (BMJ Publishing Group, 2007)
Neuberger questions our conclusions on the Allen Carr Easyway.1 As he points out, the observational data on abstinence rates are contradictory. This illustrates the difficulty of judging the efficacy of interventions without clinical trial data.